(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Abiotic environmental stresses trigger complex and adaptable reactions in plants. The salinity stress induced modifications were studied in the flowers of Ixora coccinea sourced from Bhavnagar with elevated soil salinity and for non-saline sample Ahmedabad area was chosen for flower collection. Comparative qualitative phytochemical analysis, total phenolic content and total flavonoid content was performed which indicated higher phenolic and flavonoid contents in Bhavnagar (saline) sample. Furthermore, the detection of brassinosteroids (BRs) in the saline-exposed sample suggests an adaptive response to salinity stress. Evaluation of the dyeing potential and durability of floral dyes, extracted with four solvents from both saline and non-saline samples, showed warmer colour development in non-saline extracts and cooler colour development in saline extracts. The study provides insights which may aid in the production of improved herbal dyes from I. coccinea.